Contributions of Zea mays subspecies mexicana haplotypes to modern maize - Ning Yang (Nature Portfolio, 2017)
Maize was domesticated from wild lowland progenitors that co-existed with upland subspecies in Southwestern Mexico. Here Yang et al. use a meta-assembly approach to assemble an upland mexicana genome and find evidence of introgression suggesting it contributed to modern maize adaptation